2018
DOI: 10.1088/1742-5468/aab50e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evidences of universal trap-like aging dynamics

Abstract: Trap models have been initially proposed as toy models for dynamical relaxation in extremely simplified rough potential energy landscapes. Their importance has considerably grown recently thanks to the discovery that the trap like aging mechanism is directly controlling the out-of-equilibrium relaxation processes of more sophisticated spin models, that are considered as the solvable counterpart of real disordered systems. Establishing on a firmer ground the connection between these spin model out-of-equilibriu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
(131 reference statements)
0
23
0
Order By: Relevance
“…The straight line is log(t/t w ) and fits the long time-delay data very well. In the context of the TM, an equivalent correlation function which measures the probability that the system did not leave a trap between t w and t w + t can be computed exactly and is known as the "the Arcsin law", H x (w) [34,36]. Interestingly, the Arcsin law depends on the scaling variable w = t/t w , the same which we found to describe quite well the p-spin model ageing behaviour.…”
Section: Distribution Of Trapping Timesmentioning
confidence: 62%
See 1 more Smart Citation
“…The straight line is log(t/t w ) and fits the long time-delay data very well. In the context of the TM, an equivalent correlation function which measures the probability that the system did not leave a trap between t w and t w + t can be computed exactly and is known as the "the Arcsin law", H x (w) [34,36]. Interestingly, the Arcsin law depends on the scaling variable w = t/t w , the same which we found to describe quite well the p-spin model ageing behaviour.…”
Section: Distribution Of Trapping Timesmentioning
confidence: 62%
“…Interpreting the outcome of simulations of the REM and generalisations has proved to be a very complex task. Convincing evidence for an effective TM description emerges only when the observation times are scaled exponentially with system size N [36,42,43].…”
Section: Finite Size Behaviourmentioning
confidence: 99%
“…Clearly much larger size and times would be needed to enter the asymptotic regime. Remarkably, a recent numerical study of generalised trap models [28] has shown that the very same problem also arises in simpler models with a gaussian distribution of energies. The analysis developed in [28] could be applied to the REM case in order to find more stringent evidences of trap dynamics.…”
Section: Aging Functions In the Remmentioning
confidence: 95%
“…Remarkably, a recent numerical study of generalised trap models [28] has shown that the very same problem also arises in simpler models with a gaussian distribution of energies. The analysis developed in [28] could be applied to the REM case in order to find more stringent evidences of trap dynamics. Finally in agreement with the results for the EREM, we find also in this case a more pronounced difference at low temperature between basin and configuration descriptions.…”
Section: Aging Functions In the Remmentioning
confidence: 95%
See 1 more Smart Citation